2008
DOI: 10.1136/gut.2007.140210
|View full text |Cite
|
Sign up to set email alerts
|

Increased faecal serine protease activity in diarrhoeic IBS patients: a colonic lumenal factor impairing colonic permeability and sensitivity

Abstract: Elevated colonic lumenal serine protease activity of IBS-D patients evokes a PAR-2-mediated colonic epithelial barrier dysfunction and subsequent allodynia in mice, suggesting a novel organic background in the pathogenesis of IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
250
4
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(281 citation statements)
references
References 36 publications
16
250
4
11
Order By: Relevance
“…35 Alterations in the production of these pro-inflammatory cytokines (primarily produced by monocytes and macrophages) are suggestive of an increase in innate immune activity in IBS patients. Accordingly, data collected from D-IBS patients indicate an increase in protease activity in the stool 39 and jejunal fluid 40 and an increase in NO release in the rectal mucosa, 41 indicating the potential involvement of mast cells in the increased release of inflammatory mediators. This finding is consistent with data indicating an increase in blood levels of lipid inflammatory mediators such as prostaglandin E2 and leukotriene B4, which are known to be released from newly formed mast cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Alterations in the production of these pro-inflammatory cytokines (primarily produced by monocytes and macrophages) are suggestive of an increase in innate immune activity in IBS patients. Accordingly, data collected from D-IBS patients indicate an increase in protease activity in the stool 39 and jejunal fluid 40 and an increase in NO release in the rectal mucosa, 41 indicating the potential involvement of mast cells in the increased release of inflammatory mediators. This finding is consistent with data indicating an increase in blood levels of lipid inflammatory mediators such as prostaglandin E2 and leukotriene B4, which are known to be released from newly formed mast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have reported a correlation between mast cell density and increased intestinal permeability in IBS patients. 39,71 Finally, several studies have correlated mast cell number with the severity of abdominal pain symptoms, 64,68,73,116 especially when mast cells were found close to enteric nerves. 68,73 Further investigation is required to determine the activation state of mast cells (e.g.…”
Section: Immune Activation In Ibs Patientsmentioning
confidence: 99%
“…Serine proteases become neurologically active at high levels, producing abdominal aches, muscular contractions and widespread pain. These high levels of serine proteases are not found in viral or bacterial enteritis (Gecse et al 2008). Proteases are produced by protozoa to degrade host immunological factors, such as IgA (Puthia et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the specific contribution of extracellular serine proteases and their cognate inhibitors to epithelial tight junction formation, maintenance, and regulation of barrier function is unclear. [3][4][5][6]20,21 Matriptase is a trypsin-like transmembrane serine protease encoded by the ST14 gene that belongs to the recently emerged type II transmembrane serine protease family. Orthologs of matriptase have been found in all vertebrate species analyzed to date, and homologs of the type II transmembrane serine proteases are present in bees and fruit flies.…”
mentioning
confidence: 99%